Utopia in alternative cultural movements in Latin America: a philosophical and political analysis - DÍAZ CAMACHO, Alejandro (Utopía y Praxis Latinoamericana, 2025)
In this article, I analyze the concept of utopia from a philosophical perspective and its application in alternative cultural movements in Latin America. I start from the notion of utopia as a tool of social and political criticism, exploring how these utopian aspirations have been a fundamental part of cultural movements that seek to challenge the status quo. Through a review of specific cases in the region, such as the New Chilean Song movement, popular theater in Argentina and Zapatismo in Mexico, I expose how these cultural phenomena promote ideals of social justice, equity and resistance against social structures. of hegemonic power. Additionally, I examine how rock, punk, ska, and metal in Latin America have functioned as vehicles of cultural resistance and utopian engines in their fight against oppression and inequality. My focus is on how alternative movements mobilize utopia not only as a vision of an ideal future, but as a present praxis, influencing the construction of new sociopolitical realities. Finally, I evaluate the tensions inherent to utopia and the challenges it faces in its practical application within a diverse and complex sociopolitical context such as Latin America.